UPAYA PENINGKATAN MUTU PENDIDIKAN ISLAM MELALUI MANAJEMEN MADRASAH - Muhayana Muhayana (Al-Rabwah, 2022)
The quality of Islamic education is an interesting issue to study along with its problems, while madrasa management is a tool to improve its quality. The purpose of this study is to analyze and interpret madrasa discourse, efforts to improve the quality of Islamic education through madrasa management, and the problem of improving the quality of education through madrasa management. The method used is library research by examining library materials both in the form of digital libraries and collections of books, and other documents stored in the library. The result is that madrasa management discourse is madrasa management is a process of managing, regulating, managing, and implementing planning, organizing, implementing, and evaluating madrasa education institutions. Efforts to improve the quality of Islamic education can be carried out with extensive teamwork and networks, academic and non-academic development, availability of funds and learning facilities, and teacher empowerment. The problem is that it is caused byweak madrasa management, curriculum implementation, resources, facilities and infrastructure. The hope is that madrasa managers can use the results of this study as a reference to improve the quality of Islamic education and theproblems encountered to anticipate and find solutions.